Reversible-deactivation radical polymerization of vinyl acetate mediated by tralen, an organomediator. Issue 36 (6th September 2021) - Chang, Chun-Wei; Jen, Yu-Yu; Tang, Shan-Cheng; Zhang, Pan; Chen, Changle; Peng, Chi-How
Abstract : An organic compound, tralen, has been developed as a mediator to control the radical polymerization of vinyl acetate, methyl acrylate, and N -vinyl pyrrolidone via the reversible termination mechanism. Abstract : 2, 2′-(1, 2-Phenylenebis(azanediyl))bis(cyclohepta-2, 4, 6-trien-1-one) (tralen), an organic compound with only C, H, O, and N atoms, was utilized to control the radical polymerization of vinyl acetate (VAc), in which the living character of the molecular weight not only increasing linearly with the conversion but also matching the theoretical values, and the capability of chain extension were observed. Tralen is also effective at the mediation of reversible-deactivation radical polymerization (RDRP) of methyl acrylate (MA), acrylonitrile (AN), and N -vinyl pyrrolidone ( N VP). The formation of PVAc- b -P N VP block copolymers further demonstrated the versatility of this tralen mediated radical polymerization. The mechanism study based on the MALDI-TOF, NMR, and EPR spectra of the PVAc products as well as the control studies of VAc polymerization mediated by tropone and aniline indicated that tralen forms bonds with the propagating radical by supposedly using the oxygen on the 7-membered ring to form the dormant species, which shows the single electron property and could reversibly dissociate to the PVAc radical and tralen to complete the cycle that controls the polymerization.